A qualitative study of parental modeling and social support for physical activity in underserved adolescents - Wright, Marcie S. (Oxford University Press, 2010)
This study obtained qualitative data to assess how parental role modeling and parental social support influence physical activity in underserved (minority, low-income) adolescents. Fifty-two adolescents (22 males, 30 females; ages 10–14 years, 85% African-American) participated in a focus group (6–10 per group, same gender). Focus groups were audiotaped, transcribed and coded by independent raters. Inter-rater reliabilities indicated adequate agreement [inter-rater reliability (r) = 0.84]. Themes were identified for parental role modeling and parental social support. Regarding parental role modeling, adolescents reported that parents engaged in a variety of different types of physical activities with their children such as walking, cycling and playing basketball; however, activity was infrequent. Sex differences were noted in parental social support indicating that female adolescents reported receiving more emotional and negative support for physical activity (being required to play outside with a sibling), while boys reported receiving more tangible types of support for physical activity. Adolescents also generated ideas on how to increase parental social support and in particular tangible support was highlighted as important by both males and females. This study suggests that future interventions should focus on improving parental engagement and tangible support that involve direct participation from parents in physical activities with their adolescents.